Virtual reality within the areas of sport and health - Balkó, Štefan; Heidler, Josef; Edl, Tomáš (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The aim of this study is to identify and summarize current research on virtual reality in the environments of sport and health. Despite the fact that virtual reality can be used in sports training, this issue is not sufficiently addressed in scientific research. Material and Methods. Based on keywords, studies were selected from electronic databases that addressed virtual reality (immersive and non-immersive) in an environment of sport or health. These studies were examined and their results were summarized in the present paper. Results. The analyzed publications focused mainly on the issue of rehabilitation. We also found that in many studies, authors often do not distinguish between immersive and non-immersive virtual reality. On the basis of the discovered information, it can be concluded that the environment of virtual reality can be beneficial for improvements in sports performance and motor control. Conclusions. Immersive virtual reality can be used to influence reaction times and decision making in sports. In addition, it appears to be beneficial in the training of a given motion task during rehabilitation. We realize that virtual reality cannot fully replace sports training, but it can be effectively used as a means of motor control improvement.
Keywords: sport performance; anticipation; ideomotor training; rehabilitation; motor control